Pagtatagpo sa kabilang dulo panitikang testimonial ng desaparecidos - Batnag, Aurora E.; Mercado, Emil; Padilla, Jennifer T. (Raintree Publishing, 2009)
Collection of poems, letters and testimonials of the families of victims of enforced disappearances.